Sharing information - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Since 1991 the Forestry department of the FAO has run a programme to promote NTFPs, which concentrates on collecting, analysing and disseminating technical information for the conservation of forest biodiversity. Their annual bulletin, Non-Wood...